Pengaruh Sistem Manajemen Lingkungan, Manajemen Aset, Struktur Modal, Kepemilikan Saham Publik Terhadap Kinerja Keuangan pada Perusahaan Sektor Energi Tahun 2021-2023 - Dimas Aditya Nugroho; Shafrani Dizar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the effect of Environmental Management System, Asset Management, Capital Structure, and Public Share Ownership on Financial Performance in energy sector companies listed on the IDX in 2021-2023. The research methodology used is a quantitative approach with a data collection technique, namely purposive sampling obtained from annual reports and sustainability reports of energy sector companies listed on the Indonesia Stock Exchange, so that a total sample of 141 samples was obtained. Data were analyzed using Eviews12 with the panel data regression method. The results of the study indicate that simultaneously, Environmental Management System, Asset Management, Capital Structure, and Public Share Ownership affect the company's financial performance. Partially, Environmental Management System and Asset Management have a positive effect on Financial Performance, while Capital Structure and Public Share Ownership have a negative effect on Financial Performance.